Renaissance literature and postcolonial studies - Raman, Shankar (Postcolonial literary studies., 2011)
Shows how Renaissance writers and artists struggled to reconcile past traditions with experiences of 'discovery' In what ways have colonial and postcolonial studies transformed our perceptions of early modern European texts and images? How have those perceptions enriched our broader understanding of the colonial and the postcolonial? Focusing on English, Portuguese, Spanish and French colonial projects, Shankar Raman explains how encounters with new worlds and peoples irrevocably shaped both Europeans and their 'others'. There are in-depth case studies on: the Portuguese drama and epic of Gil Vicente and Luis Vaz de CamÃæes; travel narratives and exotic engravings from Theodore de Bry's influential compilations; and the English plays and verse of Christopher Marlowe, John Donne and Richard Brome. Key Features Introduces readers to the careful reading of visual sources as a complement to textual analysis Emphasises the importance of comparative work in literary studies of colonialism: see especially the discussion of Adam Olearius' travels in Chapter 2 as well as the case studies of Portuguese literary texts and de Bry